Research Hotspots and Trends of Natural Gas Vehicles: A Visual Analysis Using CiteSpace. (June 2020) - Luo, Na; Li, Meihui; Dai, Jingqi
Abstract: Driven by the optimization of energy structure, environmental pollution control and climate change constraints, natural gas vehicles have high development potential. As a vehicle fuel, natural gas has many advantages, such as abundant reserves, excellent fuel economy and relatively less pollutants, which makes the development of natural gas vehicles more rapid. This paper uses the data analysis system (DAS) composed of Web of Science (WOS) and CiteSpace to sort out the related literature of natural gas vehicles. Through the visual analysis of 529 documents, the research hotspots and trends of natural gas vehicles from 1990 to now are found. Three important clusters are discussed in this paper, among which the future development direction of natural gas vehicles is hybrid gas-electric vehicles, in order to provide reference for the R&D and production activities of natural gas vehicles.